PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT AEON MALL INDONESIA BSD CITY TANGERANG SELATAN - Irawati, Laila; Sutarto, Bambang; Saprudin, Udin (Yayasan Education and Social Center, 2024)
The purpose of this study was to determine the Influence of Employee Motivation and Work Environment on Employee Performance of PT. Aeon Mall Indonesia BSD City Tangerang Selatan both associative partial and simultaneously. The research method used is quantitative. The sampling technique uses saturated sampling and the population and sample in this study amounted to 75 respondents. Data analysis uses validity test, reliability test, classical assumption test, regression analysis. Correlation coefficient analysis, determination coefficient analysis and hypothesis test. The results of this study both partially and simultaneously Employee Motivation and Work Environment on Employee Performance of PT. Aeon Mall Indonesia BSD City Tangerang Selatan with a contribution of 52.1%